2000
DOI: 10.3758/bf03209350
|View full text |Cite
|
Sign up to set email alerts
|

The presence of an event in the narrated situation affects its availability to the comprehender

Abstract: Narrative descriptions of events often depart from how these events would have occurred in "real time." For example, narratives often contain time shifts in which events that are irrelevant to the plot are omitted. Zwaan (1996) has shown that these time shifts may affect on-line comprehension. Specifically, they are associated with increases in processing load and a deactivation of previous information. The experiments in the present article show that the situation is more complex. Specifically, there is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
3
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 22 publications
6
43
3
7
Order By: Relevance
“…In contrast, in the present experiments, when location information was relevant to the characters' goals and actions, readers immediately updated their situation model. In a similar manner, it has been found that after a time shift, information that is no longer relevant to a narrative is suppressed (Anderson et al, 1983;Carreiras et al, 1997;Magliano & Schleich, 2000;Zwaan, 1996), whereas information that continues to be relevant remains active (Experiment 1; Anderson et al, 1983;Magliano & Schleich, 2000;Zwaan et al, 2000).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, in the present experiments, when location information was relevant to the characters' goals and actions, readers immediately updated their situation model. In a similar manner, it has been found that after a time shift, information that is no longer relevant to a narrative is suppressed (Anderson et al, 1983;Carreiras et al, 1997;Magliano & Schleich, 2000;Zwaan, 1996), whereas information that continues to be relevant remains active (Experiment 1; Anderson et al, 1983;Magliano & Schleich, 2000;Zwaan et al, 2000).…”
Section: Discussionmentioning
confidence: 79%
“…This suggests that time shifts only lead to the reduction in accessibility of temporally bound information, such as scenario-dependent characters or brief actions (cf. Anderson, Garrod, & Sanford, 1983;Zwaan, Madden, & Whitten, 2000), rather than to all concepts prior to them. More critically, we can conclude that the reduction in accessibility of characters' former locations in the time and location shift condition resulted from the change in location rather than the change in time.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the finding that readers make use of syntactic focus as a salience cue (e.g., Birch & Rayner, 1997;McKoon et al, 1993), a great deal of evidence has been accumulated that suggests that readers make use of other linguistic markers to structure their mental representation of texts. For example, morphosyntactic cues such as verb tense and aspect have been shown to foreground concepts in readers' representation of text (Carreiras, Carriedo, Alonso, & Fernández, 1997;Magliano & Schleich, 2000;Morrow, 1985;Zwaan, Madden, & Whitten, 2000). Thus, in agreement with Kintsch's (1992) argument, it appears that comprehension is influenced by a host of linguistic cues and that theories of discourse comprehension have not fully accounted for the linguistic richness of texts.…”
Section: Discussionmentioning
confidence: 79%
“…28 La majorité des autres recherches à propos de la dimension temporelle se sont intéressées à l'impact d'une rupture de la continuité temporelle sur la compréhension (Bestgen, Vonk, 1995Speer, Zacks, 2005 ;Zwaan, 1996 ;Zwaan, Madden, Whitten, 2000). Tout particulièrement, Zwaan (1996) a fait lire de brèves narrations dans lesquelles une phrase cible était introduite par un adverbial temporel comme « Un instant plus tard », « Une heure plus tard » ou « Un jour plus tard ».…”
Section: Comparaison Des Deux Conceptionsunclassified
“…Toutefois, comme pour la dimension spatiale, quelques études remettent en cause cette thèse. Zwaan, Madden et Whitten (2000) ont nuancé les conclusions de Zwaan (1996) en montrant que l'effet d'un adverbial temporel comme « Une heure plus tard » n'est pas lié à la rupture temporelle qu'il induit, mais au fait que sa longueur est suffisante pour indiquer que la situation (événement ou activité) préalablement en cours est terminée ou non. En d'autres mots, la simple présence d'un adverbial signalant une rupture temporelle importante est insuffisante pour produire une mise à jour du modèle situationnel et le ralentissement de la lecture que cette mise à jour induit.…”
Section: Comparaison Des Deux Conceptionsunclassified